Decision Support System for Selecting the Best Hotel Using the Multi-Objective Optimization Method on the Basis of Simple Ration Analysis (MOOSRA) - Mesran; Nurwahid, Fahri; Sarumaha, Farel Notafelling; Lubis, Ridha Maya Faza (International Journal of Informatics and Data Science, 2025)
Selecting the best hotel is an important decision-making process that requires careful consideration of various criteria. In this study, we use the Multi-Objective Optimization by Simple Ratio Analysis (MOOSRA) method to determine the most suitable hotel based on a set of predetermined criteria. The MOOSRA method is a multi-objective optimization technique that uses a simple ratio of the overall favorable and unfavorable criterion scores to avoid negative values and reduce the impact of large variations in criterion values. This study aims to develop a decision support system that helps customers choose the best hotel based on criteria. The MOOSRA method is applied to a decision matrix constructed from hotel attributes, and the overall performance score of each hotel is calculated using a simple ratio formula.